The Effect of Excavation Work to Soil Slope Stability - Maulana Arif; Ilpandari Ilpandari (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2022)
Excavation work is a type of work that is commonly found in many construction projects. In carrying out excavation work, it is necessary to consider stable slope conditions so that landslides do not occur during work. Common ground excavation work found on Bangka Island, especially in the city of Pangkalpinang, is kulong excavation, or sea excavation, as an effort to increase depth elevation. This study aims to determine changes in soil slope stability due to excavation work at a certain depth and slope. The study used field observation data in the form of CPT (Cone Penetration Test), hand drill, and data from laboratory analysis. Data analysis was then carried out using the Slope/W software, which is part of Geostudio 2018, to determine the safety factor for soil slopes using the Bishop and Fellenius method. The value of the safety factor produced by Slope/W determines the level of stability of the soil slope. The slope of the soil varied 15⁰, 30⁰, and 45⁰ and the excavation depth was determined to be 4 m and 8 m. The results showed that the safety factor of the 4 m and 8 m excavation depth in the same slope angle was decreasing about 23.18 % while the safety factor of the 15⁰ and 30⁰ excavation slope in the same depth was decreasing about 31.81%